Osteochondroma at Unusual Sites: A Case Series Report - Ashok Ramanujam; Annamalai Devadoss; Sathish Devadoss; Jayakumar Subbiah; Deepak Chithragar; Balaji Rajendran (Journal of Orthopedics and Joint Surgery)
Osteochondroma, the most common benign bone tumor, involves 10–15% of all bone tumors. It can occur frequently either as solitary osteocartilaginous exostosis or rarely as hereditary multiple lesions. The most common sites of occurrence are long bones of the lower arm (50%), usually the lower end of the femur and upper end of the tibia. However, involvement of the small hand and foot bones occurs in 10% of cases, pelvis in 5%, scapulae in 4%, and spine in 2%. Symptoms are not very specific. The authors present a case series of atypical sites of osteochondroma. In the present case series report, we describe a case series of osteochondroma arising from the talus, trochlea, and ribs, respectively.